Thermal and crack resistance of ceramics based on the MAX phase Ti₃AlC₂ - Boyko, Yu.I.; Bogdanov, V.V.; Vovk, R.V.; Gevorkyan, E.S.; Kolesnichenko, V.A.; Korshak, V.F.; Prikhna, T.A. (Functional Materials, 2018)
The paper discusses the conditionality of such physical properties of polycomponent oxygen-free ceramics (MAX phases), as thermal and fracture resistance, with a special physicochemical nature of the binding forces between the elements forming the MAX phase and with a specific structural state characterized by the presence of thin interlayer between the structure elements with an unordered arrangement of atoms. The results of the experimental study of some of the physical properties of Ti₃AlC₂-based materials are presented, which are consistent with the proposed concept.